O direito à educação na perspectiva da pedagogia hospitalar: a ação do pedagogo na brinquedoteca hospitalar - SILVA, Rodrigo Barra da (2025)
The objective of this research was to investigate the right to education from the perspective of hospital pedagogy, together with the action of the pedagogue in the context of the hospital toy library. The research seeks to contribute to the discussions regarding the interfaces where the pedagogy professional can act, and mainly the right to quality education for children and adolescents. The article also argues the collaboration of this professional with the medical team, influencing the improvement of the child's treatment, through the pedagogical intentionality of playing in a playful way. For the construction of this research of bibliographic analysis, searches were carried out through the Google Academic website, regarding articles already published on the subject. The theoretical contribution of reading is based on the articles by Cury (2002), Fontes (2009), Lima and Paleologo (2012), Brito and Perinotto (2014), Paula and Foltran, Angelo and Vieira (2010). As a result of this research, it can be seen that there is still absence of scientific materials related to this theme and corroborates the misinformation of this theme, and the importance of commitment to achieve improvements resulting from scientific studies.